A density functional theory analysis of the adsorption and surface chemistry of inorganic iodine species on graphitea - Ritzmann, Andrew M.; LaCount, Michael D.; Sassi, Michel; Johnson, Alyssa E.; Henson, Neil J. (Frontiers in Nuclear Engineering, 2023)
In the event of a nuclear accident, fission products may be released into the environment. The release of I-131 is of particular concern to human health. Iodine can be captured using a number of materials and frequently, this is accomplished with activated carbon impregnated with organic bases. Previous studies have used DFT and the graphite (0001) surface as a surrogate for adsorption, those studies focus on the species I•, I2, and CH3I. In this work we perform an ab initio study of the adsorption onto the surface of a graphite sheet of I2, CH3I, and inorganic acidic iodine species (HI, HOI, HIO2, and HIO3), which were selected to examine the possible effect of oxidation state on adsorption. The PBE exchange-correlation functional with D3 dispersion was employed. It was found that for molecular iodine, the iodine atoms tended to either situate above the center of a hexagonal site on the graphite or directly atop a carbon atom with the lighter components resting closer to the graphite. For each species the relative binding energies spanned the range of 21-33 kJ mol-1 and graphite-iodine distance was in the range of 3.52 to 3.93 A. In all cases we found no significant charge transfer between the iodine species and the graphite, thus we conclude that all the iodine species studied undergo strong physisorption to the graphite.